Gender and the Jubilee : Black Freedom and the Reconstruction of Citizenship in Civil War Missouri - Romeo, Sharon (Book collections on Project MUSE., 2016)
"Gender and the Jubilee offers a re-examination of the legal legacy of the Civil War, with regard to African Americans, using Missouri as a case study with broader implications. As the United States transformed from a slaveholding republic into a modern nation-state, what were the mechanisms by which citizenship was re-conceptualized? Among the multiple and contested visions of citizenship circulated during the Civil War, how did enslaved people come to be recognized as potential citizens? This book analyzes the process that produced the inclusive birthright citizenship manifested in the Fourteenth Amendment. African American women inserted themselves as members of the nation-state during the turbulent years of the Civil War crisis. They positioned themselves, rhetorically, as patriots for the Union cause. As self-identified patriots, enslaved women requested military protection from slave owners. Women fled to federal troops stationed in the city and sought a right to federal protection from abusive slave owners prior to the enactment of any emancipatory acts on the part of military policy or the federal government. This assumption of federal protection prior to the ratification of the Fourteenth Amendment, in a state outside the jurisdiction of the Emancipation Proclamation, suggests a deep investment in the ideal of a broad national citizenship that included the African American population. The litigating slave women of antebellum St. Louis, and the female activists of the Civil War period, left a rich legal heritage to those who would continue the struggle for civil rights in the postwar era. African American women would continue to play a critical role in their own liberation following the war"--Provided by publisher.